Can blindsight be superior to 'sighted-sight'? - Trevethan, C; Sahraie, A; Weiskrantz, L (2007)
DB, the first blindsight case to be tested extensively (Weiskrantz, 1986) has demonstrated the ability to detect and discriminate a range of visual stimuli presented within his perimetrically blind visual field defect. In a temporal two alternative forced choice (2AFC) detection experiment we have investigated the limits of DB's detection ability within his field defect. Blind field performance was compared to his sighted field performance and to an age-matched control group (n=6). DB reliably detected the presence of a small (2 degrees ), low contrast (7%), 4.6c/ degrees Gabor patch with the same space-averaged luminance as the background presented within his blind field but performed at chance levels at the same eccentricity (11.3 degrees ) within his sighted field. Investigation of detection as a function of stimulus contrast revealed DB's ability to detect the presence of an 8% contrast stimulus within his blind field, compared to 12% in his sighted field. No significant difference in detection performance between DB's sighted field and the performance of six age-matched control participants suggests poor sighted field performance does not account for the results. Monocular testing also rules out differences between the eyes as an explanation, suggesting that DB demonstrates superior detection for certain stimuli within his visual field defect compared to normal vision.